PkM Pengembangan Produk Olahan Rumput Laut Berbasis Aset Komunitas Petani Tradisional di Kabupaten Bulukumba - Muhammad Ikram Nur Fuady; Nurlaelah Nurlaelah; Mega Fia Lestari; Nurul Hulwanita Sharfina; Muh. Khaerunnas Dirgantara; Muh. Alfian (GUYUB: Journal of Community Engagement, 2023)
Almost all traditional seaweed farmers in Bulukumba Regency only sell seaweed in raw condition to collectors with uncertain market prices. In order to develop the quality of community life, there is a need for innovation in managing coastal assets, such as seaweed. This community service (PkM) uses the Asset-Based Community Development (ABCD) method with partners, namely the Jaya Fishermen Joint Business Group. The method of data collection was to conduct training (workshop) to seaweed farmers focusing on how to process and package seaweed into products of economic value, such as seaweed crackers / chips, then conduct in-depth interviews. The results showed that 83% of respondents were enthusiastic about the prospect of processing and packaging seaweed into crackers and chips. They also felt that the existence of processed seaweed that is attractively packaged will provide more benefits and regional attractiveness, especially Bulukumba Regency. The service team recommends that the trademark and logo of the partner as a pioneer of processing and packaging seaweed into crackers / seaweed chips with economic value be recorded legally. This can be in the form of registering trademark rights to the local government, obtaining a halal label, and registering the nutritional index to the local health and trade office by obtaining a P-IRT number.